PERAN BAHASA EKONOMI DALAM MENINGKATKAN PEMAHAMAN ISU EKONOMI DI MEDIA CETAK DAN ONLINE DI KOTA DENPASAR - Ni Putu Andini Desiyanti Laksmi; I Nyoman Bawa Bagiada; I Kadek Widiantara (Nusantara Hasana Journal, 2026)
Economic language can provide information about the economy in a more specific, precise, and structured manner. Economic terms such as inflation, deflation, and interest rates help readers better understand economic conditions. The use of economic language, both in print and online, plays a very important role in conveying information efficiently and understandably by a wide range of readers. This study aims to investigate the use of economic language in print and online media with a quantitative approach. The methods applied are content analysis and surveys, which are designed to find out how economic terms can be conveyed to the public. In this case, the researcher will collect some data from randomly drawn articles from print and online media. The discussion of economic language not only serves as a communication tool, but also as a means to understand these issues which include fiscal policy, inflation, stock market movements, and global economic developments that are often difficult for the general public to understand. With so many technical terms and complex concepts, media writers are now required to present information in a way that is clear, accurate, and easy to understand by readers with diverse educational backgrounds and economic understanding. Although print and online media are trying to simplify the language and make it easier to understand, there are still some challenges, especially for readers who do not have adequate knowledge of the language of economics. Confusion can arise when people understand the same economic term but interpret it differently, and the difference in the use of the term in different media can eliminate the meaning conveyed. Therefore, it is very important to strengthen the understanding of economic language in the community.